2013
DOI: 10.1111/epi.12502
|View full text |Cite
|
Sign up to set email alerts
|

A subset of genomic alterations detected in rolandic epilepsies contains candidate or known epilepsy genes including GRIN2A and PRRT2

Abstract: SUMMARYObjectives: Rolandic epilepsies (REs) represent the most frequent epilepsy in childhood. Patients may experience cognitive, speech, language, reading, and behavioral issues. The genetic origin of REs has long been debated. The participation of rare copy number variations (CNVs) in the pathophysiology of various human epilepsies has been increasingly recognized. However, no systematic search for microdeletions or microduplications has been reported in RE so far. Methods: Array comparative genomic hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 44 publications
6
50
1
3
Order By: Relevance
“…Indeed, two genetic ‘hits’ are not an uncommon observation in RE. In our study, we identified four patients carrying two rare risk factor CNVs, Dimassi et al described 10/47 patients with two rare CNVs26 and Reinthaler et al 27 identified 1 patient with RE carrying two hotspot CNVs and 1 family with a de novo 16p11.2 duplication and an inherited DEPDC5 mutation. In a further study, one patient with RE was found to carry a de novo GABRG2 mutation as well as an inherited GRIN2A mutation, and a second a paternally inherited 15q11.2 duplication and a maternally inherited GABRG2 mutation.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Indeed, two genetic ‘hits’ are not an uncommon observation in RE. In our study, we identified four patients carrying two rare risk factor CNVs, Dimassi et al described 10/47 patients with two rare CNVs26 and Reinthaler et al 27 identified 1 patient with RE carrying two hotspot CNVs and 1 family with a de novo 16p11.2 duplication and an inherited DEPDC5 mutation. In a further study, one patient with RE was found to carry a de novo GABRG2 mutation as well as an inherited GRIN2A mutation, and a second a paternally inherited 15q11.2 duplication and a maternally inherited GABRG2 mutation.…”
Section: Discussionmentioning
confidence: 53%
“…The heterogeneous nature of RE is underpinned by our study, where only variation at Xp22.31 is recurrent. Out of the 30 rare CNVs identified in patients with RE by Dimassi, only two overlap with our larger cohort; we both identified one patient with a maternally inherited deletion of part of UNC13C , and we identified a de novo deletion of the 16p13.11 hotspot, whereas Dimassi identified a maternally inherited duplication of the same region 26. A heterogeneous mixture of CNVs has also been identified in a cohort of patients with LKS and CSWS17, which form the severe end of the epilepsy-aphasia spectrum, with RE at the mild end.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In contrast with RE, a genetic basis for LKS and CSWSS has long remained controversial [159]. The contribution of genetic factors in the pathogenesis of this spectrum of disorders was first suggested by aCGH and then confirmed by three recent parallel studies, which have led to the identification of CNV/mutations in GRIN2A, encoding the NMDA glutamate receptor subunit gene GluN2A, in most of the families reported as well as and in 5-10% of sporadic cases [160][161][162][163]. The recurrent 16p11.2 microduplication including PRRT2 was recently shown to be a risk factor for RE [162,164,165].…”
mentioning
confidence: 99%
“…The genetic revolution has extended to the more common, age-related focal epilepsy syndrome benign epilepsy with centrotemporal spikes (BECTS; also referred to as rolandic epilepsy), long known to be genetically mediated 9 but only more recently associated with specific genes. [10][11][12][13][14][15] In this issue of Annals of Neurology, we are presented with 2 articles describing an increasingly wide phenotypic spectrum associated with mutations in the gene DEPDC5 (disheveled, Egl-10 and pleckstrin domain containing protein 5). 16,17 The protein encoded by DEPDC5 was recently identified as a member of the GATOR1 complex that exerts an inhibitory effect on mammalian target of rapamycin (mTOR)-mediated processes, such as cell growth and proliferation.…”
mentioning
confidence: 99%